The Outcome of Neurorehabilitation Efficacy and Management of Traumatic Brain Injury - Akira, Miyamoto; Yuichi, Takata; Tomotaka, Ueda; Takaaki, Kubo; Kenichi, Mori; Chimi, Miyamoto (Frontiers in Human Neuroscience, 2022)
For public health professionals, traumatic brain injury (TBI) and its possible protracted repercussions are a significant source of worry. In opposed to patient neurorehabilitation with developed brain abnormalities of different etiologies, neurorehabilitation of affected persons has several distinct features. The clinical repercussions of the various types of TBI injuries will be discussed in detail in this paper. During severe TBI, the medical course frequently follows a familiar first sequence of coma, accompanied by disordered awareness, followed by agitation and forgetfulness, followed by return of function. Clinicians must be aware of common medical issues that might occur throughout the various stages of neurorehabilitation, for example, posttraumatic hydrocephalus, paroxysmal sympathetic hyperactivity and posttraumatic neuroendocrine disorders, at each step of the process. Furthermore, we address problems about the scheduling of various rehabilitation programmes as well as the availability of current data for comprehensive rehabilitative neuropsychology techniques.